2012
DOI: 10.1073/pnas.1115169109
|View full text |Cite
|
Sign up to set email alerts
|

Ancient climate change, antifreeze, and the evolutionary diversification of Antarctic fishes

Abstract: The Southern Ocean around Antarctica is among the most rapidly warming regions on Earth, but has experienced episodic climate change during the past 40 million years. It remains unclear how ancient periods of climate change have shaped Antarctic biodiversity. The origin of antifreeze glycoproteins (AFGPs) in Antarctic notothenioid fishes has become a classic example of how the evolution of a key innovation in response to climate change can drive adaptive radiation. By using a time-calibrated molecular phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
342
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(372 citation statements)
references
References 59 publications
25
342
4
1
Order By: Relevance
“…Therefore, selective pressures acting on specific loci, as those detected by this study, might reflect past evolutionary processes leading to local adaptation and differentiation of the three Chionodraco species. As mentioned before, the divergence of the Chionodraco genus was estimated between 2 and 1.8 millions of years ago (additional result not reported in Near et al 2012), with the separation of C. myersi occurring before the divergence of C. hamatus and C. rastrospinosus (Patarnello et al 2003). The area of distribution of the three species may give some insights into the ecological cues leading to their diversification.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, selective pressures acting on specific loci, as those detected by this study, might reflect past evolutionary processes leading to local adaptation and differentiation of the three Chionodraco species. As mentioned before, the divergence of the Chionodraco genus was estimated between 2 and 1.8 millions of years ago (additional result not reported in Near et al 2012), with the separation of C. myersi occurring before the divergence of C. hamatus and C. rastrospinosus (Patarnello et al 2003). The area of distribution of the three species may give some insights into the ecological cues leading to their diversification.…”
Section: Discussionmentioning
confidence: 91%
“…Loci outside this area are potential candidates for being subject to directional selection Polar Biol of C. myersi for Ch8501 and in the branch leading to the divergence of C. rastrospinosus for loci Cr38 and Ch684. Recently, Near et al (2012) showed how the diversification of Antarctic notothenioids in the Southern Ocean, which was considered a direct consequence of AFGP evolution, was related both to freezing avoidance and to the colonization and adaptation to new ecological niches created by glacial and ice sheet activity during the Late Miocene (11.6-5.3 millions of years ago), thus at least 10 million years after the origin of AFGPs. A time-calibrated Bayesian phylogeny of 83 notothenioid species, performed by the same authors, revealed pulses of lineage diversification occurring in the most derived clades of Antarctic notothenioids, such as the genus Trematomus and the family Channichthyidae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando que el origen y diversificación de Nacella es muy posterior a la separación física del los continentes en los que actualmente se distribuye (Livermore et al 2005;Scher & Martin, 2006), la biogeografía del género no se asocia a eventos tectónicos sino que a procesos oceanográficos y climáticos más recientes (Zachos et al 2001). Los niveles de divergencia estimados en Nacella son congruentes con datos moleculares recientes estimados en peces nototenoídeos (Stankovic et al 2002;Near et al 2012) y en distintos grupos de invertebrados marinos (Page & Linse, 2002;Wilson et al 2009) que muestran procesos más recientes de diversificación que los esperados por procesos de vicarianza asociada tectónica de placas. En este contexto, los niveles de distancias genéticas en Nacella son comparables a aquellos detectados entre linajes de Antártica y Sudamérica de los géneros Astrotoma (Hunter & Halanych, 2008), Odontaster (Janosik et al 2011), Sterechinus (Poulin et al 2014) y Yoldia (González-Wevar et al 2012a;Poulin et al 2014).…”
Section: Discussionunclassified
“…Are there biases correlated with ecology or geography within clades? With the rapid accumulation of phylogenetic studies resolving the backbone (Holcroft 2005, Holcroft and Wiley 2008, Near et al 2012b, Betancur-R et al 2013, Sanciangco et al 2016, intra-ordinal (Miya et al 2013, Chen et al 2014, Dornburg et al 2015a, and intra-familial relationships (Near et al 2012a, Santini et al 2013a,b, Dornburg et al 2015b, Santini and Carnevale 2015 across most of the ray-finned fish tree of life, addressing such questions has become a possibility and represents an important first step toward understanding the evolution of circadian rhythms in vertebrates.…”
mentioning
confidence: 99%